HCMV pUL135 remodels the actin cytoskeleton to impair immune recognition of infected cells - Stanton, Richard J; Prod'homme, Virginie; Purbhoo, Marco A; Moore, Melanie; Aicheler, Rebecca J; Heinzmann, Marcus; Bailer, Susanne M; Haas, Jürgen; Antrobus, Robin; Weekes, Michael P; Lehner, Paul J; Vojtesek, Borivoj; et al. (Cell host & microbe, 2014)
Immune evasion genes help human cytomegalovirus (HCMV) establish lifelong persistence. Without immune pressure, laboratory-adapted HCMV strains have undergone genetic alterations. Among these, the deletion of the UL/b' domain is associated with loss of virulence. In a screen of UL/b', we identified pUL135 as a protein responsible for the characteristic cytopathic effect of clinical HCMV strains that also protected from natural killer (NK) and T cell attack. pUL135 interacted directly with abl interactor 1 (ABI1) and ABI2 to recruit the WAVE2 regulatory complex to the plasma membrane, remodel the actin cytoskeleton and dramatically reduce the efficiency of immune synapse (IS) formation. An intimate association between F-actin filaments in target cells and the IS was dispelled by pUL135 expression. Thus, F-actin in target cells plays a critical role in synaptogenesis, and this can be exploited by pathogens to protect against cytotoxic immune effector cells. An independent interaction between pUL135 and talin disrupted cell contacts with the extracellular matrix.
Keywords: Adaptor Proteins, Signal Transducing; Host-Pathogen Interactions; mikrofilamenta; Immunomodulation; Wiskott-Aldrich Syndrome Protein Family; Actin Cytoskeleton; rodina proteinů Wiskottova-Aldrichova syndromu; virové proteiny; Cytoskeletal Proteins; cytoskeletální proteiny; CD8-Positive T-Lymphocytes; imunomodulace; Viral Proteins; lidé; CD8-pozitivní T-lymfocyty; Immunological Synapses; interakce hostitele a patogenu; Humans; buňky NK; adaptorové proteiny signální transdukční; imunologické synapse; Cytomegalovirus; Talin; Killer Cells, Natural; talin